ANALISIS PENDAPATAN SUPIR PARIWISATA FREELANCE/ INFORMAL PASCA TRANSPORTASI ONLINE DI WILAYAH SARBAGITA PROVINSI BALI - A.A. Bagus Putu Widanta; I Wayan Wita Kesumajaya (Jurnal IPTA (Industri Perjalanan Wisata), 2019)
The development process indirectly accelerated the transformation process, Bali as one of the provinces in Indonesia also experienced a change from agrarian to industrial which was indicated by the contribution of the agricultural sector to decreasing the GDRP of Bali. Bali tourism continues to experience growth every year, which is marked by the number of tourist visits that increase every year. Rapid tourism growth requires supporting infrastructure for the needs of tourists while in Bali such as accommodation, restaurants, adequate roads, tourism objects, financial services, supply of goods and transportation services. Transportation services sector is an important requirement for tourists both for tourism and business purposes. Tourists visiting Bali Province can use a choice of public transportation modes such as bemo, Sarbagita bus, taxi and turtle transportation. The choice of transportation chosen is usually adjusted to the needs and destination. Rapidly Growing of tourism attracts many workers in Bali who are not accommodated in the formal sector to benefit the blessings of Tourism, with the limitation of capital to meet the needs of life and family needs as an informal tourism driver / freelance driver. The exsistence of freelance drivers with uncertain daily income due to intense competition, the more severe challenges in the future with the presence of online transport / taxis. Online transportation with all its advantages gets strong reactions and rejection from conventional transportation (bemo,taxi, and informal tourism driver) some of them end with the dispute. This study is not only aimed to analyzing the factors that influence the income of freelance drivers, but also examines how the influence of the presence of online transport / taxis influencing the income of freelance drivers. Primary data is used as the main estimate, with a sample of freelance tourism drivers in the Sarbagita Region of Bali Province. Estimates using a multiple linear regression models with independent variables in the form of dummy variables. The estimation results provide a complete picture of the factors that influence the income of freelance tourism drivers in the Sarbagita region of Bali Province. The results also provide an overview income of freelance drivers after the emergence of online transportation. The results of the study are also expected to be a reference for sharing parties in an effort to reduce the friction that occurs.